A multi-centre randomised clinical trial of oral hygiene interventions following stroke-A 6-month trial - Prof. Madya Dr. Normaliza Binti Ab Malik; Mohamad Yatim S.; Abdul Razak F.; Lam O.L.T.; Jin L.; Li L.S.W.; McGrath C. (Blackwell Publishing Ltd, 2024)
Maintaining good oral hygiene is important following stroke. This study aimed to evaluate the effectiveness of two oral health promotion (OHP) programmes to reduce dental plaque levels following stroke. A multi-centre randomised clinical control trial was conducted among patients hospitalised following stroke in Malaysia. Patients were randomly allocated to two OHP groups: (i) control group who received the conventional method for plaque control—daily manual tooth brushing with a standardised commercial toothpaste, (ii) test group—who received an intense method for plaque control—daily powered tooth brushing with 1% Chlorhexidine gel. Oral health assessments were performed at baseline, at 3 months and 6 months post-intervention. Within- and between-group changes in dental plaque were assessed over time. Regression analyses were conducted on dental plaque levels at 6 months controlling for OHP group, medical, dental and socio-demographic status. The retention rate was 62.7% (54 of 86 subjects). Significant within-group changes of dental plaque levels were evident among the test group (P <.001) and the control group (P <.001). No significant between-group changes of dental plaque levels were apparent (P >.05). Regression analyses identified that baseline plaque levels (adjusted ß = 0.79, P <.001) and baseline functional dependency level (adjusted ß = −0.34, P <.05) were associated with dental plaques levels at the end of the trial (6 months). Both, “Conventional” and “Intense” oral health promotion programmes may successfully reduce dental plaque during stroke rehabilitation and are of comparable effectiveness. Baseline dental plaque levels and functional dependency level were key factors associated with dental plaque levels at follow-up at 6 months.